Optical thin film design - Sarangan, Andrew (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2021)
"This title begins with the basic principles of electromagnetics and builds up to intricate optical filter designs, numerical optimization techniques, and production methods. It includes worked and practical examples, MATLAB and Python codes, instructor problem sets, as well as intuitive explanations of physical processes and design strategies"--
OCLC-licensed vendor bibliographic record.
Keywords: MATLAB; Thin films -- Optical properties; Optical films; Python (Computer program language); TECHNOLOGY / Electricity; TECHNOLOGY / Material Science; TECHNOLOGY / Lasers